ChemInform Abstract: Iron‐Catalyzed Trifluoromethylation with Concomitant C—C Bond Formation via 1, 2‐Migration of an Aryl Group. Issue 52 (24th December 2013) - Egami, Hiromichi; Shimizu, Ryo; Usui, Yoshihiko; Sodeoka, Mikiko
Abstract The title reaction starting from allylic alcohols (I) and (IV) affords α‐substituted‐β‐trifluoromethyl carbonyl compounds (III) and (V)/(VI), respectively.